Down-staging following neoadjuvant chemo-radiotherapy for locally advanced rectal cancer: Does timing of surgery really matter? - Sirohi, Bhawna (Indian J Med Paediatr Oncol, 2014)
BACKGROUND: Neoadjuvant chemoradiotherapy (NACTRT) improves local recurrence rate in locally advanced (LA) rectal cancer with no survival benefit. Pathological complete response (pCR) post-NACTRT is associated with improved outcome. Debate is ongoing as to when would be the opportune time to operate. AIM: To determine if greater down-staging can be achieved by a longer time interval from NACTRT to surgery (tumor regression score [TRS]) and whether this would impact sphincter saving surgery rates and early relapse rates. MATERIALS AND METHODS: A retrospective analysis of a prospectively maintained database of patients with LA rectal adenocarcinoma treated from January 2012 to August 2013 was carried out. One hundred and ten patients who completed NACTRT (50 Gy/25 fractions with capecitabine 825 mg/m(2) twice daily) followed by surgical resection were included. For response evaluation patients were divided into two groups, Group 1 (TRS ≤60 days, n = 42) and 2 (TRS >60 days, n = 68). Tumor down-staging, pCR rate, tumor regression grade (TRG) post-NACTRT and relapse rates were correlated with TRS. RESULTS: Of 110 patients (median age: 49 years (21-73), 71% males; 18 (16.5%) with signet ring histology) 96% patients underwent an R0 resection. Post-NACTRT, CR was attained in 5 (4.5%), partial response in 98 (89%) and stable disease in 7 (6.4%) patients. Median time from completion of NACTRT to surgery was 64.5 days (6-474). Median lymph nodes harvested were 10 (1-50). Overall, 22 (20%) patients achieved pCR. 26 (62%) patients in Group 1 compared to 36 (53%) in Group 2 underwent sphincter sparing surgery (SSS) (P = 0.357). Six patients (14%) in Group 1 and 16 (24%) in Group 2 achieved pCR (P = 0.24). Median TRG in both groups was three. CONCLUSION: Timing of surgery following NACTRT for LA rectal cancer does not influence pathological response, ability to perform SSS or disease-free survival. There is no incremental benefit of delaying the surgery though this needs to be confirmed in a prospective randomized trial.